Deconstructing the Filipino film text vis-á-vis the understanding of third cultural/cross cultural kids on Filipinoness - Rey, Myrthylle Karen Y.; Palileo, Shirley (Quezon City University of the Philippines, Diliman, 2024)
This research explores the impact of Filipino films on Filipinos who have spent a significant period of their formative years outside of the Philippines. It delves into whether or not Filipino Third Culture Kids (TCKs) and Cross Cultural Kids (CCKs) find Filipino film text significant to their understanding of Filipinoness. The study used the theoretical frameworks of cultural studies, apparatus theory, and structuralism in order to deconstruct three films, compare and contrast the lived experiences of the TCKs, evaluate how Filipino films are being represented through film language, and examine how the TCK representation contributes or not to their Filipino construct. Narrative Ethnography was the method used to engage with the participants, with the approaches of Google surveys, interviews, watch parties, and focus group discussions. In this research, participants recognized Filipino culture and their own TCK experiences through the three films used by the study. Their narratives centered on factors that influenced their own Filipinoness and how these films have shaped their perception of the Philippine culture. In conclusion, Filipino film texts were significant to the TCKs understanding of Filipinoness in relation to validating what they already know to be Filipino culture. The TCK representation in films is significant in contributing to the construct of the Filipino.
Thesis
Keywords: Motion pictures -- Philippines -- History and criticism; Identity (Psychology) in children -- Philippines